CuO/Cu composite nanospheres on a TiO2 nanotube array for amperometric sensing of glucose - Zhou, Zhiru; Zhu, Zanzan; Cui, Feiyun; Shao, Jiahui; Zhou, Hong Susan (Mikrochimica acta (1966), 2020)
A non-enzymatic glucose sensor based on the use of CuO-Cu nanospheres placed on a TiO2 nanotube (TNT) array with excellent performance is described. The electrode was fabricated by coating the CuO-Cu nanospheres onto the TNT array through electrochemical deposition. The CuO-Cu nanospheres with a diameter of ~200 nm are well dispersed on the TNT surface, which warrants smooth interaction and a 3D nanostructure with high uniformity. The modified electrode was then used for amperometric determination of glucose in 0.1 M NaOH solution. Figures of merit include (a) a typical working voltage of 0.65 V (vs. Ag/AgCl). (b) a linear range as wide as from 0.2–90 mM, (c) good sensitivity (234 μA mM −1 cm −2 ), and a 19 nM lower detection limit. The sensor is selective over ascorbic acid (AA), dopamine (DA), uric acid (UA), lactose, sucrose, and fructose. Graphical abstract